Autobiografia e letteratura per ragazzi. Tre grandi autori si raccontano - Certini, Rossella (Studi sulla Formazione/Open Journal of Education, 2017)
The essay tells about the autobiography of three authors for childhood: Mark Twain, Rudyard Kipling e Roald Dahl. Autobiographies are not used here as edu-cational or “take care” tools ut they are used as tools to interpret the novel for children and teens. They bind author and reader, within the narrative link, crucial to understanding the contents of the stories. They are full of writer’s experiences, emotions, affections, fears, thieves, names, faces... These are elements that enrich the story and tell us something more about the author’s motivations. Autobiog-raphies make the works of the authors more appealing and interesting. An erratic autobiography, a read autobiography, and a cultured for boys (Boy). The essay offers diverse and diversified perspectives for crossing the most famous works of the three authors who, starting from their existential “adventures”, interweave the intense work of narrative and writing.